Policy on the Management of Rohingya Refugees in Aceh: State Sovereignty versus Justice? - Mawardi, Chalik; Hanum, Farah (CV. Ius et Ambientis, 2023)
The influx of Rohingya ethnic refugees into Indonesia sparked controversy and rejection due to their lack of formal documentation. The influx of these migrants was intensified by the global situation, characterised by a COVID-19 epidemic classified by the World Health Organisation as a pandemic, leading several governments, including the Indonesian government, to restrict admission for foreign nationals. Despite Indonesia's non-ratification of the 1951 convention and the 1967 Refugee Status Protocol, the country still assists refugees once they have entered Indonesian territory. This is closely tied to the country's commitment to upholding the principle of protecting and guaranteeing human rights, as stated in the initial paragraph of the 1945 Constitution. This legal document aims to examine the extent to which the government and other players have fulfilled human rights in their attempts to address the Rohingya ethnic refugee crisis amidst the COVID-19 outbreak in Indonesia. The author of this legal document employs a normative juridical approach method to align relevant legal rules with ethical practises in the sector. The findings of this study demonstrate that the local government in Lhokseumawe Aceh took various measures to address the Rohingya ethnic refugees during the COVID-19 pandemic. These measures included the implementation of policies such as establishing a task force and a working group dedicated to refugee management. Additionally, there was a collaborative effort involving the local government, humanitarian organisations, and the local community to ensure that the human rights of the refugees, as individuals entitled to freedom, were upheld.